Audit Culture and Academic Production. Issue 4 (December 2016) - Welch, Anthony
Abstract The perceptible rise of an audit culture has had marked effects in higher education, including in Australia. Since their introduction in the early 1990s, academic audits have grown in size and sophistication, consuming ever more time, energy and financial resources. While supported by both governments and institutional leaders, this study reveals that the effects have significantly distorted the academic mission, favouring research published in highly ranked international journals, at the expense of local journals, and enhancing gender differences in the profession. For an English language system that is increasingly integrated into the Asia–Pacific, with a diverse academic staff, the effects are complex, and not entirely uniform. But overall, the effects have been to devalue collegiality, in the interests of re-shaping academics into self-monitoring subjects.